2020
DOI: 10.1186/s12885-020-06765-w
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors of caregivers of childhood cancer survivors: a cross-sectional study

Abstract: Background: Caregiving for childhood cancer survivors may be burdensome for caregivers and affect their physical health and health behaviors. However, studies examining health behaviors in caregivers of childhood cancer survivors are scarce. This study aimed to examine health behaviors of caregivers of childhood cancer survivors by comparing them with those of the general population, and analyze associated factors. Methods: This study included 326 caregivers of childhood cancer survivors recruited from 3 major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
4
7
0
Order By: Relevance
“…Although evidence found in cancer caregivers is still lacking, our findings align with the literature explaining that: males, higher levels of burden, stress perceived by caregivers, and lower self‐efficacy were associated with decreased HPBs 9,35,36 . The finding about gender difference is consistent with research on caregivers of childhood cancer survivors, 37 indicating male sex was associated with a higher risk of engaging in unhealthy behaviors, including physical inactivity, cigarette smoking, and alcohol consumption. The findings may be explained by socialized gender roles and gender differences in stress‐coping strategies 37 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although evidence found in cancer caregivers is still lacking, our findings align with the literature explaining that: males, higher levels of burden, stress perceived by caregivers, and lower self‐efficacy were associated with decreased HPBs 9,35,36 . The finding about gender difference is consistent with research on caregivers of childhood cancer survivors, 37 indicating male sex was associated with a higher risk of engaging in unhealthy behaviors, including physical inactivity, cigarette smoking, and alcohol consumption. The findings may be explained by socialized gender roles and gender differences in stress‐coping strategies 37 .…”
Section: Discussionsupporting
confidence: 89%
“…The findings may be explained by socialized gender roles and gender differences in stress-coping strategies. 37 This study also confirmed the findings of other caregiving studies, 9,38,39 that self-efficacy was associated with participation in HPBs. In line with Akpinar et al, 40…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…High levels of unmet need can exacerbate caregivers’ burden of cancer caregiving and jeopardize their psychophysiological function [ 37 ] and quality of life [ 28 , 38 , 39 ]. Heavy caregiver burden may foster unhealthy behaviors such as alcohol [ 40 , 41 ] and drug [ 40 ] use, which can increase the risk of developing metabolic syndrome including high levels of nonfasting glucose and triglycerides, low level of high-density lipoprotein, high blood pressure, and abdominal girth [ 42 ]. Caregiver burden and the depressive symptoms associated with caregiving can negatively affect the physical and mental health as well as quality of life of those they care for [ 43 , 44 ].…”
Section: Impact Of Caregiving On Informal Cancer Caregiversmentioning
confidence: 99%
“…However, male partners or husbands of female cancer patients who hold the norms of masculinity and face the dilemma of expressing emotional distress are also likely to develop high levels of caregiver burden and depressive symptoms [ 34 , 64 ]. The negative side of masculinity in the context of cancer caregiving may lead to a higher risk of unhealthy behaviors, such as smoking and binge drinking, in male caregivers [ 41 ].…”
Section: Factors Influencing Informal Cancer Caregivingmentioning
confidence: 99%